Investigation of deposition of nanofilms on a porous aluminium oxide substrate by mathematical modeling techniques - Vakhrushev, Aleksandr Vasilievich; Severyukhin, Aleksandr Valerievich; Fedotov, Aleksey Yurievich; Valeev, Rishat Galeevich (Computational Continuum Mechanics, 2016)
The paper presents a formulation of the problem and the methods used to study the deposition of nanofilms on a porous alumina substrate. The equations of a modified embedded-atom method that form the basis for the many-particle interaction potential are described. Aurum, argentum, iron, gallium, germanium and palladium were used as the materials to be deposited. Various mechanisms involved in the occlusion of the pores of alumina substrate with these materials were determined. Different processes of interaction between the nanostructures were observed for different types of deposited atoms. Slight sagging of nanofilms occurred in the region of a pore. The iron atoms formed nanostructures in the air above the substrate. The coating substrate occurred on island basis. Small iron nanostructures on the substrate were gradually being consolidated and grouped into larger nanostructures. Generation of iron nanostructures within the pores was observed. In the process of deposition of gallium atoms, a pore was not completely occluded as well, and a nanofilm was formed on the substrate surface as separate areas. Small gallium nanoparticles were formed on the substrate surface. Palladium generated a uniform nanofilm with a slight sagging in the pore area. When palladium atoms were deposited directly over the hole, throughout the condensation phase one could observe a hole, which was not occluded during the modeling process. In all types of deposited atoms there were single atoms, which reached the bottom of the pores. The most complete and dense filling of pores was obtained in the course of epitaxy of gallium. Pores filled by atoms can be regarded as quantum dots and used to obtain optical and electrical effects. Recommendations for obtaining nanofilm materials of different structures are presented. Nanoscale film deposition techniques show promise for some specific manufacturing processes and can be used to predict the behavior of available nanofilm materials and to create new nanofilm materials.